2017
DOI: 10.1002/ange.201612548
|View full text |Cite
|
Sign up to set email alerts
|

Alkene Hydrogenations by Soluble Iron Nanocluster Catalysts

Abstract: The replacement of noble metal technologies and the realization of new reactivities with earth-abundant metals is at the heart of sustainable synthesis.Alkene hydrogenations have so far been most effectively performed by noble metal catalysts. This study reports an iron-catalyzedh ydrogenation protocol for tri-and tetra-substituted alkenes of unprecedented activity and scope under mild conditions (1-4 bar H 2 ,2 08 8C). Instructive snapshots at the interface of homogeneous and heterogeneous iron catalysis were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 75 publications
(13 reference statements)
0
19
0
Order By: Relevance
“…[1] Unlike graphene,t ransition-metal nanosheets are very challenging to prepare owing to the lack of convenient metal precursors,t he preference for three-dimensional geometries,a nd the generally high reactivity of metal monolayers. [3,4] From ac onceptual viewpoint, 3D metal nanoclusters are models of the bulk material. Thev ast majority of transition-metal clusters contain six or more metal atoms in three-dimensional cluster geometries.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[1] Unlike graphene,t ransition-metal nanosheets are very challenging to prepare owing to the lack of convenient metal precursors,t he preference for three-dimensional geometries,a nd the generally high reactivity of metal monolayers. [3,4] From ac onceptual viewpoint, 3D metal nanoclusters are models of the bulk material. Thev ast majority of transition-metal clusters contain six or more metal atoms in three-dimensional cluster geometries.…”
mentioning
confidence: 99%
“…Small 2D metal nanoclusters can be viewed as intermediate stages of the growth of soluble metals or metal ions towards metallic monolayers ( Figure 1). [3] Recently,O hki and coworkers and our group have shown that the reaction of easily available transition-metal amide precursor complexes M{N(SiMe 3 ) 2 } 2 (M = Co,Fe) with commercial hydride sources (diisobutylaluminium hydride,D ibal-H;p inacolborane, HBpin) is ac onvenient strategy to access new topologies of low-valent transition-metal nanoclusters in high yields.Planar Co 4 ,C o 7 ,F e 4 ,F e 6 ,a nd Fe 7 clusters have been isolated and characterized. [4] An example of ap lanar,C O-free cluster is the oligohydride Rh 7 wheel (type A, Figure 1), which contains aplanar Rh core that mimics aM (111) monolayer.…”
mentioning
confidence: 99%
See 3 more Smart Citations